Bird attributes, plant characteristics, and seed dispersal of Pera glabrata (Schott, 1858), (Euphorbiaceae) in a disturbed cerrado area - Francisco,MR. (2007)
Several plant characteristics, such as fruit production, nutrient reward, secondary compounds, and fruit color display, affect fruit choice by birds. On the other hand, several bird attributes affect their efficiency as dispersers. Here we investigate the ornithochoric seed dispersal of Pera glabrata Schott (Euphorbiaceae) in a cerrado fragment in southeastern Brazil. A set of bird attributes, such as frequency of visits, number of diaspores eaten, time spent foraging, methods of taking and handling the diaspores and agonistic interactions were analyzed in order to infer about the potential of each species to act as a seed disperser. Birds were the unique seed dispersers of these oil-rich diaspores. We observed 414 bird visits during 60 hours of focal observations in five trees from December 1999 to January 2000. Twenty bird species from seven families ate the diaspores of P. glabrata, but only 14 species were considered potential seed dispersers because they swallowed the diaspores, increasing the probabilities for the seeds to be defecated and/or regurgitated away from the parent trees. The main potential seed dispersers were: Turdus leucomelas (Muscicapidae), Dacnis cayana (Emberizidae), Colaptes melanochloros (Picidae) and Elaenia spp. (Tyrannidae). We did not find any significant seasonal change in the number of visits on the fruiting trees throughout the day. We also did not find any relation between the number of visits per tree and fruit production. The most effective seed dispersers of P. glabrata were generalist birds, which have a high visiting rate, high fruit consumption rate, and spend short periods on the plants. The large number of species recorded as potential seed dispersers of P. glabrata, being most of them very abundant even in Brazilian disturbed areas, may guarantee seed dispersal of this plant in small fragments and regenerating areas.